Motor awareness and dissociable levels of action representation - Serrien, Deborah J.; Spapé, Michiel M. (Elsevier, 2011)
The present study evaluated the performance of a tracking task during which no, a small (subliminal: 20°) or a large (conscious: 60°) rotational perturbation was implemented. The instantaneous as well as carry-over effects of the perturbations were assessed. The subjective reports revealed that the subjects did not discriminate between the 0° and 20° perturbation conditions, despite increased trajectory error and directional trajectory changes in the latter than former condition, which suggests augmented error processing and task monitoring. Conversely, the 60° perturbation condition was characterized by subjective awareness in association with objective performance changes. Furthermore, a carry-over effect for the 60° but not for the 20° perturbation was observed when the distortion was removed midway into the trajectory. Together, the data underline distinct functioning of motor control and motor awareness with implications across time scales.